Cp2k: atomistic simulations of condensed matter systems. (13th June 2013) - Hutter, Jürg; Iannuzzi, Marcella; Schiffmann, Florian; VandeVondele, Joost
Abstract : Abstract : cp 2k has become a versatile open‐source tool for the simulation of complex systems on the nanometer scale. It allows for sampling and exploring potential energy surfaces that can be computed using a variety of empirical and first principles models. Excellent performance for electronic structure calculations is achieved using novel algorithms implemented for modern and massively parallel hardware. This review briefly summarizes the main capabilities and illustrates with recent applications the sciencecp 2k has enabled in the field of atomistic simulation. WIREs Comput Mol Sci 2014, 4:15–25. doi: 10.1002/wcms.1159 This article is categorized under: Software > Simulation Methods